Transcriptomic Response of Resistant (PI613981–Malus sieversii) and Susceptible (“Royal Gala”) Genotypes of Apple to Blue Mold (Penicillium expansum) Infection - Ballester, Ana-Rosa; Norelli, John; Burchard, Erik; Abdelfattah, Ahmed; Levin, Elena; González-Candelas, Luis; Droby, Samir; Wisniewski, Michael (Frontiers in Plant Science, 2017)
Malus sieversii from Central Asia is a progenitor of the modern domesticated apple (Malus × domestica). Several accessions of M. sieversii are highly resistant to the postharvest pathogen Penicillium expansum. A previous study identified the qM-Pe3.1 QTL on LG3 for resistance to P. expansum in the mapping population GMAL4593, developed using the resistant accession, M. sieversii -PI613981, and the susceptible cultivar ‘Royal Gala’ (M. domestica), as parents. The goal of the present study was to characterize the transcriptomic response of susceptible ‘Royal Gala’ and resistant PI613981 apple fruit to wounding and inoculation with P. expansum using RNA-Seq. Transcriptomic analyses 0 to 48 h post inoculation suggest a higher basal level of resistance and a more rapid and intense defense response to wounding and wounding plus inoculation with P. expansum in M. sieversii -PI613981 than in ’Royal Gala’. Functional analysis showed that ethylene-related genes and genes involved in ‘jasmonate’ and ‘MYB-domain transcription factor family’ were over-represented in the resistant genotype. It is suggested that the more rapid response in the resistant genotype (Malus sieversii - PI613981) plays a major role in the resistance response. At least twenty DEGs were mapped to the qM-Pe3.1 QTL (M×d v.1: 26,848,396 – 28,424,055) on LG3, and represent potential candidate genes responsible for the observed resistance QTL in M. sieversii – PI613981. RT-qPCR of several of these genes was used to validate the RNA-Seq data and to confirm their higher expression in MS0.